"دراسة مقارنة"إجهاض الجنين المشوَّه في الفقو الإسلامي - زغوان, مريم (University of Eloued-جامعة الوادي, 2016)
ممخص البحث ييدؼ ىذا البحث إلى د ا رسة حك إجياض الجنيف المشكه في الفقو الإسلبمي "د ا رسة مقارنة", كىذا مف خلبؿ مقارنة آ ا رء الفقياء بعضيا مع بعض, حيث ى خ لي ى ص البحث إلى: حرمة إجياض الجنيف المشكه إذا كانت التشكىات يمكف لمجنيف أف يعيش معيا كيمكف إصلبحيا بعد الكلادة؛ كيباح الإسقاط إذا كانت التشكىات خطيرة لا يرجى معيا لمجنيف حياة بحيث سيمكت قطعا عند الكلادة أك بعدىا مباشرة, أك يككف التشكه لا تستطيع الأ معو الكلادة عمى الإطلبؽ, كىذا كمو بم ا رعاة الضكابط التي نص عمييا الفقياء كالأطباء, سكاء أكاف ذلؾ قبؿ نفخ الركح فيو أ بعده. كقد قسمت ىذا البحث إلى مقدمة كفصميف كخاتمة, خصصت الفصؿ الأكؿ لمحديث عف مفيك إجياض الجنيف, كصكر الإجياض كأسبابو, ث تناكلت حك إجياض الجنيف بشكؿ عا, بينما ي عني الفصؿ الثاني بالحديث عف حقيقة تشكىات الجنيف, كالاتجاىات الفقيية في مسألة إجياض الجنيف المشكه, ث تطرقت لعقكبة جريمة الإجياض في الشريعة الإسلبمية, كختمت البحث بخاتمة بينت فييا أى النتائج ك التكصيات التي تكصمت إلييا. الكممات المفتاحية: الإجياض, جنيف, مشكه. Abstract The research is acomparative study deals withthe Islamic view about abortingthe disfigured embryothrough comparing the Jurists' opinions each other. This research is concluded with two different views. First, the aborting is forbidden if the disfigured embryo can live with its abnormalities or it can be fixed after its birth .Yet, it is permissible for necessity, as ifthe abnormalities were really dangerous thus, it will absolutely die through or after its birth or if the disfigured embryo threatens the mother' life. Definitely, choosing one view rather than the other will not be without regarding the bases of our Islamic jurisprudence and the doctors 'sayings whether before or after soul blowing., i.e., the first four months of its age. This documentis composed of an introduction, two chapters and a conclusion. the first chapter is specialized to give an exact definition to the issue ;its facets and its causes; Then I moved to a general prospect. While through the second chapter I focused onthe fact of an embryo aborting; the juristic' s opinions about the aborting penalty in the Islamic law. At the conclusion, I explained the most important upshots and recommendations that I found. Key words: Aborting, Embryo, Disfigured.
مذكرة ماستر
Keywords: اجهاض الجنين المشوه/ الفقه الاسلامي; Abortion of a deformed fetus / Islamic jurisprudence